2016
DOI: 10.1039/c5ra22873e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the oxygen evolution reaction in Mn3+-based electrocatalysts: correlation between Jahn–Teller distortion and catalytic activity

Abstract: We systematically studied the catalytic activity of the oxygen evolution reaction (OER) for the tetragonal spinel oxide Mn3-xCoxO4 (0 ≤ x < 1 and 1 < x ≤ 1.5). The OER catalytic activity of Mn3-xCoxO4 (0 ≤ x < 1) dramatically improved with an increase in Co content. We found that the OER activity of Mn3-xCoxO4 (0 ≤ x < 1) increased linearly with the suppression of the Jahn-Teller distortion. We therefore propose that the Jahn-Teller distortion plays an important role in the OER activities of compounds containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 26 publications
9
76
0
1
Order By: Relevance
“…This phenomenon can be attributed to Mn 3 + ability to remove the charge density on oxygen atom in MÀO bond, decreasing the effective charge on oxygen in MOÀH bond, particularly, on four MnÀO shorter bonds caused by Jahn-Teller distortions, [23] NiAl and NiMn LDH also exhibited the presence of m(Ni 3 -OH) configuration with 4.7 eV for proton removal as was reported previously. [11] …”
Section: Computational Resultssupporting
confidence: 68%
“…This phenomenon can be attributed to Mn 3 + ability to remove the charge density on oxygen atom in MÀO bond, decreasing the effective charge on oxygen in MOÀH bond, particularly, on four MnÀO shorter bonds caused by Jahn-Teller distortions, [23] NiAl and NiMn LDH also exhibited the presence of m(Ni 3 -OH) configuration with 4.7 eV for proton removal as was reported previously. [11] …”
Section: Computational Resultssupporting
confidence: 68%
“…17 mV dec −1 lower than that of Cu plate, implying the improved OER rate on a Cu/PVdF‐HFP fibrous catalyst. The obtained Tafel slope value is little larger than the layered transition metal catalyst (e. g. 40 mV dec −1 for NiFe‐LDH in 1 M KOH), comparable with the transition metal oxide catalyst (e. g. 60 mV dec −1 for Mn 3 O 4 in 1 M KOH) as well as the precious metal oxide catalysts (e. g. 55 mV dec −1 for RuO 2 and 91 mV dec −1 for IrO 2 in 0.5 M KOH), and smaller than the most of the perovskite‐based catalysts (70 mV dec −1 for LaCoO 3 and 91 mV dec −1 for La 0.8 Sr 0.2 O 3 in 1 M KOH). It is unlikely that the unique fibrous structure of Cu/PVdF‐HFP fiber catalyst affects the energetics of the OER; the much higher specific OER activity of Cu/PVdF‐HFP fiber compared to the Cu plate is probably due to the synergetic effect between Cu and PVdF‐HFP …”
Section: Resultsmentioning
confidence: 77%
“…A similar study in base by Hirai et al. compared pure Mn 2 O 3 for the OER by using Mn 2 O 3 mixed with different amounts of Co oxide . The specific activity of the various Co/Mn oxide ratios were compared at a potential of 1.76 V versus a reversible hydrogen electrode (RHE), and the results demonstrated that, with increasing amounts of Co oxide compared to Mn 2 O 3 , an increase in OER performance was observed.…”
Section: Introductionmentioning
confidence: 90%
“…measured the Jahn–Teller distortion, which occurs when the axial bonds are shorter than the elongated bonds in respect to the central atom, and found that a suppression of the Jahn–Teller distortion occurred with increasing Co content. Therefore, they suggested that the suppression of the bonds to a more compressed structure is likely to contribute to the better OER performance of the Co/Mn oxide compared to pure Mn 2 O 3 . Other elements including palladium and gold have also been used to increase the OER activity of Mn oxide …”
Section: Introductionmentioning
confidence: 99%